Penelope Popper, book doctor - Buzzeo, Toni.; Christy, Jana (Madison, Wis. : Upstart Books, 2011)
Penelope desperately wants to be a doctor, obtaining everything she needs but the patients, and Ms. Brisco, the librarian, teaches Penelope how to mend old books in need of care.
2.4
K-3.
K-3
Keywords: Books -- Conservation and restoration -- Juvenile fiction; Libraries -- Juvenile fiction; Books -- Conservation and restoration -- Fiction; Libraries -- Fiction; Books -- Conservation and restoration -- Fiction; Libraries -- Fiction; Picture books for children